Research on the Optimization Design of Solar Energy-Gas-Fired Boiler Systems for Decentralized Heating - Ming Tao; Yanzhe Yu; Huan Zhang; Tianzhen Ye; Shijun You; Mengting Zhang (Energies, 2021)
Solar energy-gas-fired boiler heating systems attract widespread attention due to their eco-friendly technologies and reasonable prices. In order to promote the application of a solar energy-gas-fired boiler system for decentralized heating, this study proposed a holistic method to optimize the combination of equipment specifications and control strategies of the system. A detailed mathematical model of the hybrid energy system was developed and validated by experiments to simulate various operating conditions and evaluate the optimal design results. A case study was conducted in Tianjin, China, and optimal schemes were obtained. The influence of different factors on the system’s annual comprehensive energy efficiency ratio (AEER) and annual cost (AC) were studied by sensitivity analysis; the results showed that the solar collector area was extremely valuable for the optimization of AEER and AC. The results of this study provide a reference for the optimization design of the solar energy-gas-fired boiler system, which is beneficial to the promotion of the utilization of solar energy.